2011
DOI: 10.1007/s10103-011-0924-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-power 808-nm laser irradiation inhibits cell proliferation of a human-derived glioblastoma cell line in vitro

Abstract: It has been reported that low-power laser irradiation (LLI) can modulate various biological processes including cell proliferation. Some reports suggest that LLI interferes with the cell cycle and inhibits cell proliferation, while others suggest that LLI has a stimulatory effect. Mechanisms underlying the effects of LLI remain unclear. Since the effects of LLI on cancer cells are not well understood, with the aim of developing an LLI therapy for malignant glioblastoma, we investigated the effects of LLI on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 31 publications
2
29
1
4
Order By: Relevance
“…PBM (808 nm; 5.85 and 7.8 J/cm 2 ) had an inhibitory effect on the proliferation of a human hepatoma cell line [86], and Sroka et al [87] reported that glioblastoma/astrocytoma cells exhibited a slightly decreased mitotic rate after PBM at 805 nm and 5–20 J/cm 2 . Similarly, 808-nm laser irradiation with an energy density of more than 5 J/cm 2 inhibited cell proliferation of glioblastoma cells in vitro [88]. Moreover, Al Watban et al [89] observed growth inhibition of cancer cell lines at relatively high cumulative PBM doses.…”
Section: Pbm Effects On Tumor Cell Linesmentioning
confidence: 99%
“…PBM (808 nm; 5.85 and 7.8 J/cm 2 ) had an inhibitory effect on the proliferation of a human hepatoma cell line [86], and Sroka et al [87] reported that glioblastoma/astrocytoma cells exhibited a slightly decreased mitotic rate after PBM at 805 nm and 5–20 J/cm 2 . Similarly, 808-nm laser irradiation with an energy density of more than 5 J/cm 2 inhibited cell proliferation of glioblastoma cells in vitro [88]. Moreover, Al Watban et al [89] observed growth inhibition of cancer cell lines at relatively high cumulative PBM doses.…”
Section: Pbm Effects On Tumor Cell Linesmentioning
confidence: 99%
“…Under the right irradiation conditions cell growth inhibition has been reported. Under long irradiation times the growth and proliferation of a human glioblastoma cell line was significantly inhibited [148]. Studies led by Fonseca have found evidence of genetic damage [149], increased mRNA and protein expression involved in DNA repair and genomic stabilization [150], and increasing occurrence of both apoptosis and necrosis [151] in white blood cells and myoblasts exposed to 808 nm light.…”
Section: Direct Optical Excitation Of 1o2mentioning
confidence: 99%
“…dose-dependent manner (25). Frigo et al reported that 660-nm LPLI at 21 J/cm 2 negatively affected 3T3 murine fibroblast cells, as it increased cell death and inhibited cell proliferation (9).…”
Section: Innovationmentioning
confidence: 99%